Petroleum geology and exploration in Levant Basin, Eastern Mediterranean - Kun TIAN; Jinyin YIN; Dapeng WANG; Jinrui GUO; Chongzhi TAO (Shiyou shiyan dizhi, 2020)
This paper analyzes hydrocarbon accumulation conditions, defines hydrocarbon plays and discusses their hydrocarbon accumulation models using geological and geophysical data and an international petroleum exploration and production database, with an approach of integrated geological investigation and play quick analysis. The intention is to identify favorable areas for exploration in the Levant Basin which experienced three main tectonic evolution stages, including rifting, passive continental marginal and tectonic inversion. It can be divided into three plays in Miocene, Pliocene and Mesozoic reservoirs. The Miocene play is the most important. The controlling factors of Miocene play are Oligocene-Miocene biogenic gas, high-quality submarine fan turbidite sand reservoir that related to Palaeo-Nile drainage system, large-scale anticline traps formed during tectonic inversion and Messinian evaporite as a regional caprock. High-quality channel turbidite sand reservoirs related to small-medium sized submarine canyons and short-distance gas migration are key factors that control hydrocarbon accumulation of the Pliocene play. Potential Cretaceous deepwater clastics and Jurassic carbonate build-ups on highs comprise a speculative Mesozoic play in deep water. Three plays are favorable regimes for future exploration, and the Miocene play in deep water and the under-explored Mesozoic regime are of high exploration potential.